FLOW SIMULATION ON LOCKING MODE IN TANDEM COMPRESSOR CASCADE - Терещенко, Ю.М.; Дорошенко, Е.В.; Ластивка, И.А. (Science-based technologies, 2015)
In work are represented the results of flow simulation on locking mode in tandem compresor cascade at angles of attack in range –15º…–30º at inlet fixed Mach number Мw1= 0,9; 0,808; 0,65. The redistribution of the flow in the inter-blade channel has significant influence for large negative angles of attack on the occurrence of locking mode of viscous gas flow. This is due to the emergence of the critical flow regime in a slot channel between the profiles of the first and second rows. In work are represented corrected method for calculation of locking mode in tandem compresor cascade. Method takes into account the influence of the redistribution the flow parameters in the inter-blade channel of tandem compresor cascade. Comparison of the results of numerical simulations and theoretical calculations showed good agreement. Accuracy of calculation is 1,65…2,4%.